EDUCAÇÃO PARA AS RELAÇÕES ÉTNICO-RACIAIS: O QUE PENSAM AS PROFESSORAS DE EDUCAÇÃO INFANTIL EM UMA INSTITUIÇÃO PÚBLICA DO INTERIOR PAULISTA - Crisley de Souza Almeida Santana (2021)
This study is the result of a master's degree research carried out in the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul - Três Lagoas campus, within the research line: Education, Childhood and Diversity. The research aimed at identifying in the speeches of Kindergarten teachers how Ethnic-Racial Relations Education has been developed in their practices. To support the work, the educational policies that provide the basis for the implementation of affirmative practices in schools were presented, as well as the main documents that support the actions in Early Childhood Education. In addition, it sought to elucidate the relevance of the Sociology of Childhood for the recognition of Ethnic and Racial diversity. The research was carried out in the city of Santa Mercedes in a basic education school that provides Early Childhood Education, but only with teachers who work with children between four and five years old. (Pre I and Pre II). The analyses indicated that the practices around the theme have been established amid contradictions and advances. The contradictions occur in the teachers' conceptions that limit their practices in punctual activities and on the understanding of what the commitment to racial equality is. The advances in their speeches show that in their practices, even if in a subtle way, the teachers have been acting towards the valorization of the black child, establishing clippings of experiences that make the work with ERER possible. Thus, we conclude that it is necessary a continuous deepening in in-service training on the theoretical field of sociology of childhood and ethnic-racial relations since early childhood education constitutes a space of socialization, which goes through racial relations, which recognizes the child as a social being, active, who has individuality, able to position himself in the face of experiences in society.